Uji UJI EFEKTIVITAS GEL EKSTRAK ETANOL 70% GETAH GAMBIR (Uncaria gambir. Roxb) dan BETADINE TERHADAP LUKA SAYAT PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR - sulasmi sulasmi (Jurnal Penelitian Farmasi & Herbal, 2022)
Gambir (Uncaria gambir. Roxb) contains flavonoids, tannins, saponins and alkaloids that can help heal wounds. One of the main ingredients that gambir contains is catechins . Catechins are flavonoid compounds with anti-inflammatory, antioxidant and antibacterial properties derived from Gambir. This study aimed to compare wound healing time between ethanolic extracts of 70% gambir resin gel (Uncaria gambir. Roxb) with betadin preparations in male Sprague dawley rats (Rattus norvegicus). A total of 9 white rats (Rattus norvegicus) strain Sprague dawley were divided into 3 groups, a negative control group for gel base treatment and a positive control group for gambir sap gel preparations (Uncaria gambir. Roxb) betadine comparison group. This study was conducted by experimental method with a post-trial controlled group design. Each group is colored with group preparations, the treatment is carried out 3 × 1 every day. Wound healing time was analyzed by a one-way Anova test on spss. Healing ingroup I was 10.6 days, in group II, 10.3 days in group III and 9.3 days.